YIELD AND HETEROSIS EFFECT OF TOMATO FIRST GENERATION (F1) HYBRIDS (Journal of Universal Science Research, 2023)
In the article, in 2018-2019, the yield indicators of tomato hybrids of the first generation at the Surkhandarya Scientific Experimental Station were studied. According to the results, Surkhan 142 x Taramata, Taramata x Volgogradsky 5/95, Surkhan 142 x Volgogradsky 5/95 and L-31 have the highest heterosis efficiency (33.7-74.2%) in terms of total and early yield and total yield. x Surkhan 142 hybrids were separated.High (15.3-23.0%) heterosis efficiency in terms of early yield was observed in hybrids Taramata x Volgogradsky 5/95, Surkhan 142 x Taramata and MJ-46 x Surkhan 142.These hybrids are also notable for their resistance to the tuber nematode. These hybrids can be recommended for production after certain trials and are a valuable starting source for the development of better resistant cultivars and hybrids with valuable economic traits.